IGNATIAN PEDAGOGY PARADIGM TO IMPROVE STUDENTS’ COMPETENCE, CONSCIENCE, COMPASSION, COMMITMENT AND INTEREST ON PHYSICS RESEARCH METHODOLOGY COURSE - Suparno, Paul (Sanata Dharma University Yogyakarta, 2019)
This research investigates the influence of the Ignatian pedagogy paradigm (PPI)Â toward the development of competence, conscience, compassion, commitment, and interest of physics students on their learning about research methodology course. The sample of this research is 48 students who took research methodology course. This research uses PPI as treatment. The instruments that were used are a questionaire,Â observation, and documentation. The research uses quantitative and qualitative analysis. To compare the result of pretest and posttest, t-dependent test is used. The result of the research is that the competence, conscience, compassion, and interest of students significantly increase; but their commitment is not significantly improved.DOI: doi.org/10.24071/ijiet.2019.030105